Pelatihan Penggunaan Aplikasi Mendeley Untuk Manajemen Referensi Karya Ilmiah Bagi Mahasiswa Universitas Sains dan Teknologi Semarang - Zusrony, Edwin; Dewi, Maya Utami; Imaliya, Tri; Siswanto, Siswanto; Kholifah, Siti; Maulan, Puteri Anindya; Magriyanti, Arie Atwa; Veliyanti , Reni; Manalu, Gibson; Sumaryanto, Sumaryanto (Journal Of Human And Education (JAHE), 2024)
Publication of scientific work in the SINTA accredited journal requires every author to learn a reference management application such as the Mendeley application. When citing reference sources for scientific works, all SINTA accredited journals require the use of the reference manager application for writing citations and bibliography. This development in writing scientific papers has made the community service team try to provide training in using the Mendeley application to students. The aim of this activity is to provide an understanding of the function of the Mendeley application to optimize the writing of scientific papers such as final assignments or research journals. This activity was carried out online using Zoom Meeting and was attended by sixth semester students at the Semarang University of Science and Technology. This activity took place over three sessions, consisting of: how to install the Mendeley application, introduction to the Mendeley application features, and how to cite Mendeley from various literary sources. The impact of the activity showed that the participants were very enthusiastic, as proven by 85% of the participants who were independently able to install and integrate the Mendeley application with Ms. Word and doing literature citations.